Age Related Changes of Human Uterus-A Postmortem Study - Uddin, MS; Al-Muhaimin, M; Begum, N; Sultana, Z (Medicine Today, 2013)
The uterus is an essential principal accessory female reproductive organ whose function is to receiving and rearing an egg within its mucosa, nourishes and protects the embryo, and expels it at the proper time. Uterus related clinical conditions such as leiomyomas also known as myomas or fibroid and carcinoma cervix are major medical conditions within aging population. Detailed morphological knowledge is essential for proper diagnosis and management of uterine diseases. Study design was descriptive type of study. Place and period of study was department of anatomy, Sylhet M A G Osmani Medical College, Sylhet, from July 2006 to June 2007. Present study was performed on 50 autopsied human uterus of age ranging from 1 to 65 years. The samples were collected from unclaimed dead bodies that were autopsied in the morgue of Department of Forensic Medicine of Sylhet M A G Osmani Medical College, Sylhet. The samples were divided into four age groups. Group A (1-12 years), Group B (13-24 years), Group C (25-46 years) and Group D (46-65 years). All samples were studied morphologically. Statistically significant positive correlation was found between age breadth and thickness of uterus. There were changes in the morphology of uterus in relation to age. DOI: http://dx.doi.org/10.3329/medtoday.v24i2.15010 Medicine Today 2012 Vol.24(2): 70-72